A construção da paternidade no vazio da ausência paterna: um estudo sobre como os pais que não tiveram a presença paterna constroem a paternidade com os seus filhos - Pucci, Romina Carla (2012)
This research was carried through in São Paulo (SP) and had as objective to understand as men who had not coexisted the paternal presence had constructed the proper paternity. The interest for the subject appeared by means of the perception of the increase of monoparental families, commanded for women and of the amount of men who if had become parents without having had the paternal presence. Its specific objectives had been to understand the participation of the mother and/or another figure as mediating (s) in the situation of paternal absence; to understand which the easinesses and difficulties in the exercise of the paternity for men who had not coexisted the proper father; to understand as if constitutes the affective and emotional development of the son of absent father. One was about a qualitative research of exploratory level, characterized as Study of Collective Case, of which two men had participated who, today, they are parents, but that they had not coexisted the proper father. For the collection of data the half-structuralized interview was used and its end was requested to the participants who wrote a letter its parents. The results had shown that a common characteristic to the participants and, probably, decurrent in part of the paternal absence is the unreliability and the lack of belief in itself exactly. On the other hand, empty left by the lack of the father, revealed a fertile land so that the participants could construct social substitutes who gave sensible account and to this absence, as for example, the study